ANALISIS KEBIJAKAN PENANGGULANGAN TUBERKULOSIS (TB) DI KABUPATEN SUKOHARJO MENGGUNAKAN PENDEKATAN GAP ANALYSIS DAN CRITICAL SUCCSESS FACTOR (CSF) - Fahmi Hakam (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2018)
Sukoharjo is a regency in Central Java that is having high rank of TB case. In 2016, the sufferers of TB were452 with the total of death were 16 people. In 2017, the sufferers were 335. One of the control indicators was Case Detection Rate (CDR). The established-policy needed medical support facility. The professional employees will support the continuity of health service for the concerned society. The aim of this research was to analyze the rule and fact of TB’s tackling in Sukoharjo regency by looking at the side of government organization needs and the plan had made. The approach was needed in examining the plan of strategy and tackling policy by having framework related to the method and systematic technique. The long-term target of this research was the result of the TB’s situation analysis that could be the input for the stakeholders dealing with designing the priority scale as the arrangement of Regional Action Plan “Rencana Aksi Daerah (RAD)” or as the advocacy material for civil society group in tackling TB so that its prevention and treatment could be managed and supported by all stakeholders in Sukoharjo regency. The method used by the researcher were GAP Analysis and CSF (Critical Sucses Factor). The cause of the high and low of TB’s finding in Sukoharjo regency were categorized into direct and indirect factors. One of them was the absence of special law in regency or regional. The other issue was about human resources. Besides, many health service facilities had not fulfilled the DOTS (Directly Observed Treatment Short-course) which influenced TB’s achievement in Sukoharjo regency.Keywords : Tuberculosis, TB’s Policy, CSF, GAP Analysis